Congenital granular cell tumor: an unusual case report - Yailit Del Carmen Martinez Vargas; Rani Iani Costa Gonçalo; Danielle Machado Farias; Lélia Maria Guedes Queiroz (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Congenital granular cell tumor is an uncommon benign oral lesion of uncertain histogenesis that affects the alveolar ridge region of newborns. The present study aims to report an unusual congenital granular cell tumor case, emphasizing clinical, morphological, and immunohistochemical aspects. A 10-day-old newborn patient attended the stomatology service with a nodular pedunculated lesion of normal color located in the anterior region of the superior alveolar ridge. Thus, the diagnostic hypothesis was congenital epulis, and an excisional biopsy was performed. Histopathological analysis revealed features consistent with the diagnosis of congenital granular cell tumor. In addition, we performed immunohistochemical staining for vimentin, Ki-67, and S100. The patient has been under follow-up with no clinical signs of recurrence. Due to its rarity, the analysis of congenital granular cell tumor's clinicopathological characteristics enables an adequate diagnosis and treatment.